Investigasi Kinerja Kepala Sekolah dan Operator dalam Meningkatkan Mutu Sekolah di Sekolah Dasar Negeri 3 Jerowaru - Kamaruddin, Kamaruddin (FONDATIA, 2025)
The quality of education is significantly impacted by the operator's and principal's performance. There is a performance disparity between the two at certain institutions, nevertheless, because of the principal's extremely poor performance and lack of recognition and care for the operator. The effectiveness and efficiency with which an operator performs their job is referred to as operator performance. In order to recognize accomplishments, pinpoint areas that require improvement, and inspire operators, this performance evaluation is often conducted on a regular basis. Thus, the study's goals are 1) to ascertain how well the operator and principle performed in raising the standard of education at Jerowaru 3 Elementary School, and 2) to ascertain how much the principal valued the operator's contribution to raising the standard of education. Descriptive qualitative research is what this kind of study is. Techniques for gathering data include documentation, interviews, and observation. The operator and principle of Jerowaru 3 Elementary School served as the study's participants. According to the study's findings, the performance of the principal and operator in raising the standard of instruction at Elementary School 3 Jerowaru was investigated. This investigation involved a methodical procedure used to gather, examine, and assess data in order to comprehend a specific incident or circumstance. Therefore, the significance of the aforementioned inquiry is linked to the provision and participation in the establishment of a school quality improvement program based on full accountability, for the purpose of continuity.